2022
DOI: 10.3390/medicina58080977
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Associated Guillain–Barré Syndrome: A Report of Nine New Cases and a Review of the Literature

Abstract: Background: Guillain–Barré syndrome (GBS)—a rare condition characterized by acute-onset immune-mediated polyneuropathy—has been registered as a neurological manifestation of COVID-19, suggesting a possible link between these two conditions. Methods: We report a case series of patients with COVID-19-related GBS hospitalized in the Neurology Department of Colentina Clinical Hospital, Bucharest, Romania, between March 2020 and March 2021. Several variables were analyzed, such as the mean interval between the onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…There are some papers reporting GBS in SARS-CoV-2 individuals who had no upper respiratory tract infection symptoms. 20,21,23,28 Furthermore, Zhao et al and Cea et al also reported cases where the latency period was 0 days as GBS symptoms preceded COVID-19 symptoms. 25,32 The postponement of GBS neurological features is related to the pathogenesis of GBS in SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 98%
“…There are some papers reporting GBS in SARS-CoV-2 individuals who had no upper respiratory tract infection symptoms. 20,21,23,28 Furthermore, Zhao et al and Cea et al also reported cases where the latency period was 0 days as GBS symptoms preceded COVID-19 symptoms. 25,32 The postponement of GBS neurological features is related to the pathogenesis of GBS in SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, patients without an otherwise identifiable cause for GBS should be screened for COVID, as the autoimmune reaction can occur even in the absence of infectious symptoms. 12 The prevalence of COVID-associated GBS has declined since the introduction of COVID vaccines, however, cases are still being reported. 13 Furthermore, investigations are underway to determine the risk of GBS resulting from the COVID vaccine itself.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of GBS within two weeks rather than 2-4 weeks after the infectious agent mimics the picture seen with the Zika virus. This suggests a proinflammatory state leading to direct nerve damage rather than the presence of autoantibodies [34].…”
Section: Guillain-barré Syndrome (Table 5)mentioning
confidence: 99%